Դաշինքների մեկնաբանման տեսահայեցակարգային մոտեցումները արևմտյան գիտական դիսկուրսում - Ղևոնդյան, Ալեն (YSU Journal of International Affairs, 2016)
The alliances and their policy traditionally played an important role in international relations. They were often part of national security and national interest. And it is natural that the concept of alliances has been widely discussed, interpreted and defined by different theories of international relations (realism neorealism, idealism, constructivism and institutionalism), as well as by different authors, who developed the concept by using the structural and functional analysis method. As a result, we have a variety of definitions that contradict each other and lead to misunderstanding of the concept. In this article, we try to define the fundamentalcharacteristics of the concept of alliances by analyzing the western scientific literature about the topic. We also suggest a new comprehensive definition of the concept of alliance, which is theoretically thorough and concurrently practical.
Keywords: alliance, coalitions, political realism, balance of power, NATO